Design of Compound Harmonic Transmission Device for Cone-beam Oral CT Machine - Zhen Zhang; Fengshou Zhang; Weidong Song (Jixie chuandong)
Aiming at the high precision of the transmission system of the scanning device in the cone-beam oral CT diagnostic equipment，the ordinary transmission device is difficult to meet its use requirements. The oral CT machine developed in China has high noise and low positioning accuracy，harmonic transmission has the advantages of smooth transmission and high transmission accuracy. Combined with the characteristics of planetary gear transmission with strong anti-shock and vibration capabilities，a composite harmonic transmission device for cone beam oral CT scanning device is designed. Three-dimensional modeling is performed using the three-dimensional design software SolidWorks，and Adams kinetic simulation software is introduced for simulation experiments. The results show that the design has fast response，smooth rotation，high transmission accuracy，and meets medical requirements.